Partner and Household Factors Associated with Breastfeeding Practice: A Systematic Review - Supriatin, Supriatin; Astriani, Ni Made Dwi Yunica; Heri, Mochamad; Sadli, Mohamad (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2024)
The role of partner and family in breastfeeding practice is still rare. Previous studies were more likely to discuss the impact of infant and mother factors. This study aimed to examine the role of partner and family factors associated with breastfeeding factors. This systematic review includes 18 journal articles from four databases such as PubMed, ScienceDirect, SCOPUS, and Scholar Google. The selection of journal articles was described in the PRISMA diagram. The findings revealed that the factors from partners including education, support, knowledge about breastmilk, age, and occupation, and factors from family and household including food security, family support, family intention, and type of family play a role in influencing the breastfeeding practice. Since this study only focused on partner and household factors, the findings emphasize the significant role of partner and family in improving the breastfeeding practice. The government and related stakeholders can take an important role in contributing to increasing the participation of partners or husbands in breastfeeding practices such give parental leave to support the wife during exclusive breastfeeding.